Black Widow Deadly origin - Cornell, Paul.; Raney, Tom.; Leon, John Paul. (New York Marvel Publishing Inc., 2010)
As Natalia Romanova, aka the Black Widow, tries to get to the bottom of a plot to kill her and those she loves, she relives the events in her life that have brought her to this point.
Contains material originally published in magazine form as Black Widow : deadly origin #1-4"--Tp verso.
Keywords: Women spies -- Comic books, strips, etc; Science fiction comic books, strips, etc; Superheroes -- Comic books, strips, etc